Mô hình toán học của bộ điều khiển mở với việc bổ sung tri thức và đầu ra là một tập lồi - Dũng, Lê Bá (Journal of Computer Science and Cybernetics, 2016)
A mathematical model of fuzzy controller with simultaneous update knowledge is describded in this paper.